Social Theory of Fear - Skoll, Geoffrey (Springer Nature, 2010)
Fear has long served elites. They rely on fear to keep and expand their privileges and control the masses. In the current crisis of the capitalist world system, elites in the United States, along with other central countries, promote fear of crime and terrorism. They shaped these fears so that people looked to authorities for security, which permitted extension of apparatuses of coercion like police and military forces. In the face of growing oppression, rebellion against elite hegemony remains possible. This book offers an analysis of the crisis and strategies for rebellion.